2016
DOI: 10.5796/electrochemistry.84.854
|View full text |Cite
|
Sign up to set email alerts
|

Surface Layer and Morphology of Lithium Metal Electrodes

Abstract: The surface morphology of the electrodeposited lithium metal from electrolyte solutions containing electrolyte additives: fluoroethylene carbonate (FEC), vinylene carbonate (VC) and lithium bis(oxalate)borate (LiBOB), were investigated. All the film forming additive improved the surface morphology. The FEC especially shows the most uniform surface morphology compared with the other electrolyte additives and the additive-free electrolyte. The surface analyses of the lithium metal were conducted using X-ray phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 26 publications
0
48
1
Order By: Relevance
“…The detected signals are displayed by dotted lines, while the backgrounds, the deconvoluted peaks, and the sums are displayed by solid lines. The peak assignments for the spectra are carried out by referring multiple sources: the spectra we took with reference samples, NIST X-ray Photoelectron Spectroscopy Database, and past reports 16,51,52 and listed in Table I. Relative elemental composition is estimated by integration of peak area and listed in Table II. The XPS spectra and the elemental composition for the LiBH 4 /THF also prove that the LiBH 4 /THF produces a tiny amount of the surface layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detected signals are displayed by dotted lines, while the backgrounds, the deconvoluted peaks, and the sums are displayed by solid lines. The peak assignments for the spectra are carried out by referring multiple sources: the spectra we took with reference samples, NIST X-ray Photoelectron Spectroscopy Database, and past reports 16,51,52 and listed in Table I. Relative elemental composition is estimated by integration of peak area and listed in Table II. The XPS spectra and the elemental composition for the LiBH 4 /THF also prove that the LiBH 4 /THF produces a tiny amount of the surface layer.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 We previously reported that fluoroethylene carbonate (FEC) stabilizes the surface layer, and a solvate ionic liquid delays the dendrite formation. 16,17 However, the dendrite formation still remains as a fundamental challenge on the lithium metal anodes. 13,[18][19][20] In the case of the alloy/intermetallic anodes, the volume expansion and shrinkage of the active material leads pulverization of the particles during the charging and discharging processes.…”
mentioning
confidence: 99%
“…The result of SEM observation revealed that the improved homogeneity of SEI. Actually, FEC and LiBOB were reported to contribute to the formation of compact and uniform SEI with improved morphology 2224 . In addition, the improved morphological homogeneity of the SEI surface in the presence of LiBr has also recently reported 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above growth mechanisms of Li dendrites, many promising methods have been proposed to suppress the undesired electrochemical behavior, including liquid electrolyte modification [22][23][24][25] , solid-state electrolyte [26][27][28][29] , artificial SEI [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] (including fluorinated SEI [35][36][37][38][39][40] and sulfurized SEI [41][42][43][44][45] ), and nanostructured frameworks [46 , 47] . Liquid electrolyte modification improves significantly the ionic conductivity, but most liquid electrolytes can react with the fresh Li dendrites, leading to low coulombic efficiency [48] .…”
Section: Introductionmentioning
confidence: 99%